Spatial distribution of radon concentration and risk evaluation through consumption of groundwater in the District of Kotli, Azad Jammu and Kashmir - Said Muhammad; Nizam Ullah; Alaa Ahmed (Kuwait Journal of Science)
Radon (222Rn) is naturally readily water-soluble, posing a cancer risk to the exposed community. Human exposure in the community may occur via 222Rn intake in drinking water. Groundwater is used for drinking and other domestic purposes in the region. Higher concentrations of 222Rn in groundwater have been reported near Kotli district, Azad Jammu, and Kashmir. This investigation aimed to measure 222Rn concentrations in groundwater and evaluate the associated risk assessment for children and adults in the Kotli district. 222Rn concentrations were measured in randomly collected groundwater samples of Kotli (n = 25) and Sehnsa (n = 15) towns in the Kotli district using the portable Radon Detector (RAD7, Durridge Company, United States of America). Among the studied areas, the Sehnsa showed a higher average 222Rn concentration (7.6 ± 0.2 Bq/L) in groundwater compared to Kotli (6.0 ± 1.9 Bq/L). The average concentrations of 222Rn were found within the recommended limit (11.1 Bq/L) of the United States Environmental Protection Agency (USEPA), except for 10% of sampling sites. 222Rn concentrations were used for the calculation of total effective dose for ingestion and inhalation pathways (EwTotal) values for infants (24.5 ± 7.5 and 30.7 ± 0.9 μSv/a), children (18.1 ± 5.5 and 23.5 ± 0.7 μSv/a), and adults (18.1 ± 5.5 and 22.7 ± 0.3 μSv/a) in the Kotli and Sehnsa, respectively. This study noted that EwTotal and estimated lifetime cancer risk (ELCR) values were found within the World Health Organization (WHO) and European Commission (EU) acceptable limits (<100 μ Sv/a and 0.1 × 10−3).